Laboratory mice born to wild mice have natural microbiota and model human immune responses - Rosshart, Stephan P.; Herz, Jasmin; Vassallo, Brian G.; Hunter, Ashli; Wall, Morgan K.; Badger, Jonathan H.; Mcculloch, John A.; Anastasakis, Dimitrios G.; Sarshad, Aishe A.; Leonardi, Irina; Collins, Nicholas; Blatter, Joshua A.; et al. (Science, 2019)
Laboratory mouse studies are paramount for understanding basic biological phenomena but also have limitations. These include conflicting results caused by divergent microbiota and limited translational research value. To address both shortcomings, we transferred C57BL/6 embryos into wild mice, creating “wildlings.” These mice have a natural microbiota and pathogens at all body sites and the tractable genetics of C57BL/6 mice. The bacterial microbiome, mycobiome, and virome of wildlings affect the immune landscape of multiple organs. Their gut microbiota outcompete laboratory microbiota and demonstrate resilience to environmental challenges. Wildlings, but not conventional laboratory mice, phenocopied human immune responses in two preclinical studies. A combined natural microbiota- and pathogen-based model may enhance the reproducibility of biomedical studies and increase the bench-to-bedside safety and success of immunological studies.
CRIS-Team Scopus Importer:2022-12-14